`Magic Numbers for Sales Management’: Simple Arithmetic for Sales Practitioners and Strategists - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Singapore Management University marketing professor John Davis has just published his third book, Magic Numbers for Sales Management. Davis has led marketing teams in several major American corporations, and is also the founder of a consulting and training company, Brand New View. Magic Numbers for Sales Management pulls together 50 of the most important sales metrics and formulae in a format that is accompanied by examples from many of today’s leading organisations. Davis spoke to Knowledge@SMU about his book as well as sales management in general.